Molecular analysis of YR genes for yellow rust resistance in bread wheat (Triticum aestivum L. Em Thell) (Bangladesh Journal of Botany, 2019)
Investigation was conducted to evaluate 210 recombinant inbred lines (RILs) of bread wheat to identify Yr genes using SSR markers and response to stripe rust reaction. Recombinant inbred lines were screened under epiphytotic conditions and data in terms of per cent leaf area infected were recorded using Modified Cobb’s Scale. A total of seven Yr genes, namely Yr7, Yr18, Yr26, Yr29, Yr36, Yr47 and Yr53 were found to be linked to yellow rust resistance. Out of 40 Yr specific SSR markers, seven (Xgwm130 (Yr7), Xbarc 352 (Yr18), Xgwm 11 (Yr26), Xwmc 44 (Yr29), Xwmc 149 (Yr53), WKS1_I (Yr36) and Xcfb309 (Yr47) were found to be polymorphic in parental genotypes and RIL population indicating the presence or absence of Yr genes. Three RILs namely, 51, 52, 55 had largest number of resistant genes (4Yr genes) followed by six lines namely, RIL No. 20, 21, 23, 29, 39, 53 had 3Yr genes having disease score (0S). These RILs may be utilized for incorporation of specific Yr genes in well adapted genotypes for improvement of disease resistance in bread wheat.